Investigation of the efficacy and safety of lung biopsy plus microwave ablation for a solitary suspected malignant pulmonary nodule after radical mastectomy - Xing, Chao; Li, Peishun; Yang, Sen; Man, Qirong; Zhang, Xusheng; Yuan, Qianqian; Hu, Miaomiao; Bai, Yunling; Zhang, Kaixian (Frontiers in Oncology, 2025)
PurposeTo evaluate the safety and efficacy of CT-guided lung biopsy combined with microwave ablation (MWA) for solitary suspected malignant pulmonary nodules in post-radical surgery breast cancer patients.Materials and methodsThis retrospective study included 37 post-radical surgery breast cancer patients with solitary suspected malignant pulmonary nodules, treated with CT-guided lung biopsy and MWA between January 2014 and December 2018. Institutional review board approval was obtained. Clinical outcomes and complications were analyzed.ResultsPathological results identified primary lung cancer in 5 patients (13.5%, 5/37) and metastatic invasive ductal carcinoma (breast origin) in 30 patients (81.1%, 30/37). Major complications included pneumothorax (n=8, 21.6%), chest pain (n=6, 16.2%), and hemoptysis (n=4, 10.8%). For metastatic cases, 2-, 3-, and 5-year survival rates were 86.2%, 58.3%, and 35.3%, respectively. The median progression-free survival after MWA was 35 months (range: 4–72; 95% CI: 24.53–46.48), and median overall survival was 44 months (95% CI: 32.55–55.45).ConclusionCT-guided lung biopsy combined with MWA is a safe and effective approach for managing solitary suspected malignant pulmonary nodules in post-radical surgery breast cancer patients.